Over and Above. - LEE, LYDIA (Architectural Record, 2022)
BUILDING TYPE STUDY 1,040 RECORD HOUSES AFTER SPOTTING an open lot east of downtown Sacramento, Erica Bergsma, a local developer of multifamily infill housing, knew that it would be a great place to build a house for her own family. Instead of locating the bedrooms above the public spaces, the architects put the kitchen, dining, and living areas on the top floor, with an open-plan arrangement and a terrace running along its length. Milwaukee - based Johnsen Schmaling Architects had already collaborated with Bergsma to design six other projects for her company, Indie Capital, including Broadway Housing in Sacramento (RECORD, October 2019).